Dampak Prasangka dalam Circle Pertemanan Mahasiswa Bimbingan Penyuluhan Islam A Semester VI Universitas Islam Negeri Sumatera Utara - Ainul Mardiyah; Inez Echa Aurel Nasution; Anni Mardia Sagala; Dini Syafitri Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Humans as social beings cannot be separated from interaction with each other, which then forms social relationships such as friendship. The circle of friendship among students has a great influence on behavior, mindset, and character development. However, in the dynamics of this relationship, it is not uncommon for prejudice to appear—negative assessment of individuals or groups without an objective basis. This research aims to examine the forms of prejudice, causative factors, and their impact in the circle of friendship of Islamic Counseling A students in Semester VI of the State Islamic University of North Sumatra. Although Islamic Extension Guidance students are equipped with the values of empathy, openness, and counseling skills, prejudice is still found in their friendship environment. Prejudices that are allowed to develop can be an obstacle in building healthy and productive social relationships. This research is expected to provide theoretical and practical contributions in building a healthier, reflective, and more friendly relationship in accordance with Islamic values. Qualitative research method, by interviewing three speakers who are students majoring in Islamic Counseling, class A, Semester VI, North Sumatra State Islamic University, Medan.